Financial access and digital services within agri-food value chains in Bangladesh - Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan; Islam, Saiful; Wagner, Julia (International Food Policy Research Institute, 2023)
Agri-food value chains are a crucial element of food systems and local economies around the world. Existing estimates show that intermediary agri-food value chain actors—the operating enterprises that transport and transform food from the farmgate to retailers—account for 60 to 75 percent of value-added produced by the entire agricultural sector of an economy.